Pembuatan Game Royal Coin - Saputra, Ridho; Aswandi, Aswandi; Amri, Amri (Jurnal Teknologi Rekayasa Informasi dan Komputer, 2023)
Games have become popular among the community, including forms of entertainment, support for them, computers have provided the full potential to do one of the creative industries that is growing very rapidly and the interest of many people is the game. This game is designed using Unity, randomly raises obstacles in games in 3 different directions. When playing a game, you will get 3 health aids to use the game if there is a collision with the obstacle in the game. Score reputation for obstacles. Constraints will appear randomly in the game. Keywords : Game, Score, Random Obstacle